2014
DOI: 10.1177/2158244014522071
|View full text |Cite
|
Sign up to set email alerts
|

The Leadership Dimension in Information and Communication Technology Adoption in African Libraries

Abstract: The article focuses on leadership challenges in adaptation to Information and Communication Technologies (ICTs) in African libraries. It identifies and discusses the need for adequate leadership styles and behavior in the bid to adapt effectively to new technologies. Online survey, observation arising from personal professional practice experience, personal communication, and interview methods were used to gather data for the study. Older library professionals, many of whom are still very visible across the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Few managers conscious of internal CSR, have proactively planned the business expansions and presented it to their directors, whereas others neglected it. The present research is in agreement with the previous study (Oyelude & Oladele, 2014), which focuses on the need for relevant training of their employees in particular companies and industries. Instead of going into complicated statistical and mathematical calculations, successful managers have converted threats into opportunities using entrepreneurial capabilities.…”
Section: Implications and Contributionssupporting
confidence: 92%
See 1 more Smart Citation
“…Few managers conscious of internal CSR, have proactively planned the business expansions and presented it to their directors, whereas others neglected it. The present research is in agreement with the previous study (Oyelude & Oladele, 2014), which focuses on the need for relevant training of their employees in particular companies and industries. Instead of going into complicated statistical and mathematical calculations, successful managers have converted threats into opportunities using entrepreneurial capabilities.…”
Section: Implications and Contributionssupporting
confidence: 92%
“…Information and communication technology may have an adverse quantitative impact on employment (UKEssays, 2013), which reflects that the implementation of information technology may lead to unemployment. A case illustrates that harnessing the synergy of ideas-mentoring, training, and refreshers are needed for the adoption of information and communication technology in a department (Oyelude & Oladele, 2014). Due to the reduction of paperwork and emergence of automation, businesses boon expediently, and the tasks which were performed by human beings manually are performed by computer systems such as answering of phone calls by systems replaced receptionists and telephone operators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data revealed that perceived ease of use of the library system had a significant impact on perceived usefulness, which ultimately led to a behavioural intention to use. Oyelude and Oladele (2014) discussed ICT adoption in African libraries and identified the need for ICT deployment and use. It is noted that some senior library leaders not only resist changes towards technology adoption but also prevent the younger professionals from performing to their full capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this study reveal that transformational and transactional leadership styles portend safety for libraries in the face of COVID-19 pandemic. This is because leadership traits that support transformational and transactional leadership offer hope for the libraries (Akor, 2014; Oyelude and Oladele, 2014; Nwaigwe, 2015). Riggs (2001) and Igbaekemen (2014) emphasised that prospective leadership crises in libraries can be eliminated through the application of transformational and transactional leadership styles.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents rated their leadership style as more transformational and transactional than laissez-faire. In a study of the leadership dimension in information and communication technology adoption in African libraries, Oyelude and Oladele (2014) found that the most ubiquitous leadership styles needed for ensuring suitable adaptation to ICT in libraries include: team-building (88.4%), sharing leadership (65.1%), exemplary leadership (58.1%), persuasive leadership (39.5%), assertive leadership (32.6%) and benevolent leadership (14%). Ogbah (2013) examined the leadership style and organisational commitment of librarians and support staff in some selected academic libraries in Delta State, Nigeria.…”
Section: Leadership Styles Of Library Leadersmentioning
confidence: 99%